2005
DOI: 10.1089/cpb.2005.8.513
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adolescents Engagement in Risky Internet Behavior

Abstract: The present study used data from the SAFT (Safety, Awareness, Facts and Tools) Singapore survey, a national survey of 1,124 youths aged 12-17, to explore the issue of risk on the Internet. We investigated factors that influence adolescents' engagement in risky Internet behavior, in particular, meeting face-to-face someone they first encountered online. The adolescents ranged from ages 12 to 17, with a mean of 14.32 (SD = 1.37); 49.6% of the adolescents were girls. The study utilized a 93-item survey that was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 9 publications
7
116
0
10
Order By: Relevance
“…The myth of the digital generation implies that digital technologies have developed a status of such paramount importance among the youth in their everyday lives that there is no longer a digital divide within this generation. This myth is supported by surveys indicating that more than 90% of youths are using the Internet (Liau, Khoo, & Ang, 2005;Livingstone & Bober, 2005;USC ASCDF, 2005;Zamaria & Fletcher, 2007). Even in Malaysia, 90% of urban youths are using the Internet (Soh, Chew & Ang, 2008).…”
Section: Ethnicity and Internet Usementioning
confidence: 94%
“…The myth of the digital generation implies that digital technologies have developed a status of such paramount importance among the youth in their everyday lives that there is no longer a digital divide within this generation. This myth is supported by surveys indicating that more than 90% of youths are using the Internet (Liau, Khoo, & Ang, 2005;Livingstone & Bober, 2005;USC ASCDF, 2005;Zamaria & Fletcher, 2007). Even in Malaysia, 90% of urban youths are using the Internet (Soh, Chew & Ang, 2008).…”
Section: Ethnicity and Internet Usementioning
confidence: 94%
“…An in-depth study on parental mediation among younger children found that parents tend to be confident in their internet parenting, but the author suggests that this confidence is not always substantiated and may be biased due to the low actual parental involvement in children's internet use (Shin, 2015). Liau, Khoo, and Ang (2005) found that parental control did not have any effect on the experience of online contact risks, but children who voluntarily disclosed their potentially high-risk online contacts showed less online risk behavior. A study by Law, Shapka, and Olson (2010) found that children who voluntarily disclosed their internet behavior to their parents were less likely to bully online.…”
Section: Performing Parental Mediationmentioning
confidence: 99%
“…Some studies, which include aspects of the parent-child internet communication, support the idea that this is highly relevant when it comes to understanding internet parenting and safe internet use. For example, child disclosure about online experiences has been linked to less engagement in online risk behavior (Law et al 2010;Liau et al 2005), and a good perceived quality of internet communication with the parents can be a buffer against engagement in online verbal aggression among adolescents with high internet use (Appel et al 2014). Furthermore, it is important to acknowledge that parental knowledge-generating practices do not occur in isolation from such broader parent-child dynamics.…”
Section: Sources Of Parental Knowledgementioning
confidence: 99%